2015
DOI: 10.1371/journal.ppat.1005158
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Viral and Mutational Spectrum of Endemic Burkitt Lymphoma

Abstract: Endemic Burkitt lymphoma (eBL) is primarily found in children in equatorial regions and represents the first historical example of a virus-associated human malignancy. Although Epstein-Barr virus (EBV) infection and MYC translocations are hallmarks of the disease, it is unclear whether other factors may contribute to its development. We performed RNA-Seq on 20 eBL cases from Uganda and showed that the mutational and viral landscape of eBL is more complex than previously reported. First, we found the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 82 publications
(95 reference statements)
9
151
0
1
Order By: Relevance
“…Furthermore, lytic antigen expression was confirmed by immunohistochemical staining for BMRF1 early lytic protein, a DNA polymerase factor essential for lytic virus replication, observed in 9/13 (70%) of our EBV+ DLBCL cases (Figure ). This was in agreement with similar observations found in other B‐cell lymphomas, where it was proposed that lytically infected B‐cells secrete factors that may promote tumourigenesis, including growth and angiogenesis factors and immunosuppressive cytokines.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, lytic antigen expression was confirmed by immunohistochemical staining for BMRF1 early lytic protein, a DNA polymerase factor essential for lytic virus replication, observed in 9/13 (70%) of our EBV+ DLBCL cases (Figure ). This was in agreement with similar observations found in other B‐cell lymphomas, where it was proposed that lytically infected B‐cells secrete factors that may promote tumourigenesis, including growth and angiogenesis factors and immunosuppressive cytokines.…”
Section: Resultssupporting
confidence: 92%
“…Even though latency programs predominate in EBV‐driven tumours, recent evidence suggests that lytic EBV replication has certain pathogenic role, at least in the early phases of cell transformation . Abate et al observed RNAseq in an endemic BL cohort, the expression of lytic genes suggesting a noncanonical latency program of the virus with a subset of viral episomes initiating lytic reactivation . Particularly, in DLBCL, the EBV lytic cycle is by and large unexplored, but recently, Morishima et al described higher IgG antibody titres against lytic antigens, which were considered as a marker of EBV reactivation, in a series of 13 EBV+ DLBCL patients older than 50 years .…”
Section: Resultsmentioning
confidence: 99%
“…These genes also implicate DNA repair in terms of oncogenesis where we identify 3 previously undescribed genes ( MSH6, RAD50 , and PRKDC ) involved in double strand repair and nonhomologous end joining. The analysis presented here of BL patients from Kisumu, Kenya was underway when a similar study was published involving 20 Ugandan patients (24). Therefore, we reevaluated our analysis to determine if we could validate their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Even though deregulated expression and subsequent mutations of MYC gene severely alter the DNA binding efficiency of this transcription factor, these do not appear to be sufficient for tumorigenesis (20). The search for additional driver mutations in sBL has yielded several candidate tumor suppressors and oncogenes (2123), however; eBL primary tumor biopsies have not been studied at a genome-wide level until recently with limited numbers of cases (24). The most common driver mutations in coding regions appear to occur in the transcription factor TCF3 (E2A) and its inhibitor ID3 .…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences, however, were seen in the expression of BCR signaling pathway genes in tumors with and without a dominant, productive IGH rearrangement. RNAseq variant analysis revealed sequence variants in genes previously reported to be mutated in BL, including ID3, TP53, SMARCA4, ZNF587, and FOXO1, 24,25,[28][29][30] as well as 14 genes that are mutated in other cancers, including NOTCH1, PAX5, and TFAP4 ( Figure 1D; supplemental Table 2). Two tumors with a polyclonal IGH repertoire and a clonal IGK/IGL rearrangement by HTS of gDNA carried mutations in several genes mutated in other BL tumors, including TP53, POMC, COL6A3, and BSCL2, supporting the diagnosis of BL in these cases.…”
Section: Transcription Of Bl Tumor Igh and Igk/igl Rearrangementsmentioning
confidence: 99%